A new species of the assassin bug genus Rihirbus (Hemiptera: Heteroptera: Reduviidae) from Vietnam - Lam, Truong Xuan; Hoa, Bui Thi Quynh; Linh, Ha Ngoc; Cai, Wanzhi (Zootaxa, 2020)
Rihirbus kronganaensis sp. nov. (Hemiptera: Heteroptera: Reduviidae: Harpactorinae) is described from central highlands of Vietnam. A key to the species of Rihirbus Stål, 1861 is presented.